(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
One of the issues around which much ink has been spent in criminal matters concerns the fundamental principles around which the legal-penal subsystem is identified and distinguished from other constitutional subsystems present in the legal system. This is an important issue, as the principles of Criminal Law mean true values that will be materialized by the other legal and penal rules, not only those contained in the Penal Code, but also those contained in extravagant legislation, especially in the legal microsystems that contain criminal rules. Keywords: Penal Principles; Constitutional; Right; Criminal; Axiomatic.